2016
DOI: 10.3727/152599516x14745497664352
|View full text |Cite
|
Sign up to set email alerts
|

Social Identity in Serious Sport Event Space

Abstract: Sport events offer valuable experiences in distinctive settings, and serve as settings for social identity formation. Drawing on the literature from a range of disciplines, events characteristics are seen to provide spaces for the cocreation of values, liminality, communitas, flow experiences, and authenticity. It is suggested that sport events facilitate career progression in relation to serious leisure and the development of social identification. This article provides further insight about the nature of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…fan and or spectator). The transcendental encounter echoes the theoretical and conceptual perspectives of 'flow' in sport, proposed by Csikszentmihalyi and Csikszentmihalyi (1998), as Lee et al (2016) state:…”
Section: The Nature Of Liminality and Sport Eventsmentioning
confidence: 81%
See 3 more Smart Citations
“…fan and or spectator). The transcendental encounter echoes the theoretical and conceptual perspectives of 'flow' in sport, proposed by Csikszentmihalyi and Csikszentmihalyi (1998), as Lee et al (2016) state:…”
Section: The Nature Of Liminality and Sport Eventsmentioning
confidence: 81%
“…The co-creation element can be located in Pine and Gilmore's (1999) escapist experience domain 1 as the emphasis here is upon active engagement and a state of immersiveness is encountered, which is reflective of liminoid liminality. McDonald and Karg (2014) and Lee at al. (2016) recognise this experiential value of co-creation for marketing of the sport event because there is an opportunity to influence fan behaviour in terms of consumption and participation.…”
Section: The Nature Of Liminality and Sport Eventsmentioning
confidence: 94%
See 2 more Smart Citations
“…Their research revealed a general consensus amongst host communities that events have "fairly substantial economic, entertainment, social and development benefits." Events are also powerful modes of communication, engagement and affiliation, and researchers have explored the ways sport events help to nurture community development (Warner & Dixon, 2011), shared values and social identities (Lee et al, 2016). The ways events generate social capital is now widely recognised too, even beyond the events literature.…”
Section: Events and Sustainabilitymentioning
confidence: 99%